Limit States of Materials and Structures Direct Methods - Weichert, Dieter; Ponter, Alan (Springer Netherlands : Imprint: Springer, 2009)
To determine most exactly the carrying capacity of a structure or a structural element has always been a major concern to any design engineer. For safety sensitive structures this implies not only situations of normal service conditions but also states near to failure or post-critical states in order to better prevent accidents by appropriate design. Among the rational design tools available to engineers, for this purpose the so-called "direct methods", embracing in particular limit- and shakedown analysis, have always been particularly attractive due to the fact that they allow to determine in a constructive way directly the limit loads of a structure. This holds true for simple loading by proportionally applied mechanical and thermal loads, but also for the more complicated situation of variable loading even in the case when the loading history is not deterministically given. The tremendous progress in computation over the last years has contributed very largely to the development of direct methods. They have left the realm of ad-hoc computing and can be used today for post-processing in combination with commercial design tools. Far from being comprehensive, given this very active field of scientific research and development, the papers presented in this book give an account of some of the most advanced results achieved over the last years by leading scientists in the field. This way, the book is meant to help the practical engineer to choose the right tool for his safety analysis of critical structures and to stimulate researchers to enter this most interesting field, reaching from highly abstract concepts up to the essential questions of practical engineering.